Women's attitudes toward certification logos, labels, and advertisements for organic disposable sanitary pads: results from a multi-city cross-sectional survey - Hayeon Kim; Jinyoung Jung; Yun-Kyoung Song; Taegwon Chang; Sungmin Park; Jiwon Park; Kyungim Kim (BMC, 2022)
Abstract Background This cross-sectional study evaluated women's attitudes toward the certification logos, labels, and advertisements for organic disposable sanitary pads (OSPs) and investigated what could be the main reason for them. Additionally, the present study examined whether a relationship could be found between these attitudes and OSPs purchasing behavior. Methods This study was conducted using a self-reported online survey of Korean adult women who have purchased OSPs. The study questionnaire had four sections, covering (1) characteristics of OSP purchasing behavior, (2) attitudes toward OSP certification logos, labels, and advertisements, (3) demand on government and companies for proper management, and (4) respondent's sociodemographic information. The Cronbach's alpha value of the questionnaire was 0.857. Results A total of 500 respondents completed the questionnaire. Overall, high reliability was found for the certification logos (3.73 ± 0.61), labels on the product packaging (3.71 ± 0.63), and advertisements of OSPs (3.41 ± 0.62). Respondents indicated that these had fairly positive effects on their decision-making regarding product reliability, product image, and their own purchasing behavior. The aspects most frequently affected from the informants were safety to human health. All attitudes toward OSP certification logos, labels, and advertisements that were evaluated in this study became more positive in the direction from non-buyers to occasional buyers and to habitual buyers (all P < 0.05). The most significant demand from the respondents for OSP companies and the government was to clearly indicate hazardous ingredients on the OSP packaging (42.0%) and to strengthen the sanctions for false advertising (37.8%), respectively. Conclusions The results of this study clearly indicate the importance of using certification logos, labels, and advertisements in the OSP market. These results can be utilized by OSP companies to improve the effectiveness of their marketing strategies or by policy makers and certifying bodies to manage the informants properly in the OSP market.